Use of anticoagulants and antiplatelet agents in stable outpatients with coronary artery disease and atrial fibrillation. International clarify registry - Fauchier Laurent; Greenlaw Nicola; Ferrari Roberto; Ford Ian; Fox Kim M.; Tardif Jean-Claude; Tendera Michal; Steg Gabriel Ph.; CLARIFY Investigators; Jánosi András; Forster Tamás; Merkely Béla Péter (2015)
Background: Few data are available regarding the use of antithrombotic strategies in coronary artery disease patients with atrial fibrillation (AF) in everyday practice. We sought to describe the prevalence of AF and its antithrombotic management in a contemporary population of patients with stable coronary artery disease. Methods and Findings: CLARIFY is an international, prospective, longitudinal registry of outpatients with stable coronary artery disease, defined as prior (≥12 months) myocardial infarction, revascularization procedure, coronary stenosis >50%, or chest pain associated with evidence of myocardial ischemia. Overall, 33,428 patients were screened, of whom 32,954 had data available for analysis at baseline; of these 2,229 (6.7%) had a history of AF. Median (interquartile range) CHA2DS2-VASc score was 4 (3, 5). Oral anticoagulation alone was used in 25.7%, antiplatelet therapy alone in 52.8% (single 41.8%, dual 11.0%), and both in 21.5%. OAC use was independently associated with permanent AF (p<0.001), CHA2DS2-VASc score (p=0.006), pacemaker (p<0.001), stroke (p=0.04), absence of angina (p=0.004), decreased left ventricular ejection fraction (p<0.001), increased waist circumference (p=0.005), and longer history of coronary artery disease (p=0.008). History of percutaneous coronary intervention (p=0.004) and no/partial reimbursement for cardiovascular medication (p=0.01, p<0.001, respectively) were associated with reduced oral anticoagulant use. Conclusions: In this contemporary cohort of patients with stable coronary artery disease and AF, most of whom are theoretical candidates for anticoagulation, oral anticoagulants were used in only 47.2%. Half of the patients received antiplatelet therapy alone and one-fifth received both antiplatelets and oral anticoagulants. Efforts are needed to improve adherence to guidelines in these patients. Trial Registration: ISRCTN registry of clinical trials: ISRCTN43070564. © 2015 Fauchier et al.